Canadian securities regulation - Johnston, David L. (LexisNexis Canada, 2025)
"A team of expert authors provides an authoritative exploration of the Canadian securities regulatory system, its historical underpinnings and the practical ramifications of its administration and enforcement. Thoroughly revised and updated, this edition features several reorganized chapters that reflect the evolution of securities regulation in Canada and current issues facing today’s regulators and market participants."-- Provided by publisher.